2020
DOI: 10.1039/d0tb01964j
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin loaded layered double hydroxide nanocomposites for tumor specific photothermal–chemodynamic therapy

Abstract: With the inspiration to develop new cancer nanotherapeutics by repurposing old drugs, in the current study, a novel two dimensional nanomedicine namely Mn doped, dihydroartemisinin (DHA) loaded layered double hydroxide...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…In other words, two types of transition metal elements are used to achieve efficient CDT via Fenton and/or Fenton‐like reaction at the same time. The currently reported dual metal ions‐mediated strategies are based on manganese/iron, [ 352–358 ] copper/iron, [ 359–365 ] copper/manganese, [ 366,367 ] etc.…”
Section: Applications Of Cdt In Anticancer and Antibacterial Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, two types of transition metal elements are used to achieve efficient CDT via Fenton and/or Fenton‐like reaction at the same time. The currently reported dual metal ions‐mediated strategies are based on manganese/iron, [ 352–358 ] copper/iron, [ 359–365 ] copper/manganese, [ 366,367 ] etc.…”
Section: Applications Of Cdt In Anticancer and Antibacterial Therapiesmentioning
confidence: 99%
“…In another example, Lu and co‐workers developed MnMgFe‐LDH (LDH was the abbreviation of layered double hydroxide) loaded with DHA (termed LDH/DHA) for enhanced PTT/CDT. [ 355 ] First, LDH containing Mg 2+ and Fe 3+ was synthesized through a simple co‐precipitation approach. Then the authors conducted the partial isomorphic substitution between Mn 2+ and Mg 2+ to obtain MnMgFe‐LDH.…”
Section: Applications Of Cdt In Anticancer and Antibacterial Therapiesmentioning
confidence: 99%
“…In contrast, undersized LDHs are easily to fill in the pores between collagen fibers, and in this case, it would be unrealistic to expect the formation of surface-conductive layer. LDHs can be produced via different methods, including co-precipitation, [28][29][30] hydrothermal, [31,32] calcination-reconstruction, [33,34] ion exchange, [35] and template methods. [36] Hydrothermal method was selected to prepare LDHs in this work because the produced LDHs had high crystallinity and narrow particle size distribution.…”
Section: Fabrication Of Pedot:pss/ldhs/leather Composite Sensormentioning
confidence: 99%
“…In addition, PDA aids in PTT through synergistic enhancement of CT and CDT effects by increasing cell death via heat generation from the specific light source. Lu et al reported dihydroartemisinin-loaded manganese ion-doped magnesium-Iron-LDH NCs for synergistic CDT/PTT [15]. The developed NC's showed tremendous photothermal properties with a photothermal conversion efficacy of up to 10.7% [15].…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al reported dihydroartemisinin-loaded manganese ion-doped magnesium-Iron-LDH NCs for synergistic CDT/PTT [15]. The developed NC's showed tremendous photothermal properties with a photothermal conversion efficacy of up to 10.7% [15]. In another study, Sun et al reported indocyanine green intercalated copper (Cu) substituted LDH for combinational PTT/PDT therapy to inhibit tumor growth in vivo.…”
Section: Introductionmentioning
confidence: 99%